2017
DOI: 10.1371/journal.pone.0178621
|View full text |Cite
|
Sign up to set email alerts
|

Effective treatment options for musculoskeletal pain in primary care: A systematic overview of current evidence

Abstract: Background & aimsMusculoskeletal pain, the most common cause of disability globally, is most frequently managed in primary care. People with musculoskeletal pain in different body regions share similar characteristics, prognosis, and may respond to similar treatments. This overview aims to summarise current best evidence on currently available treatment options for the five most common musculoskeletal pain presentations (back, neck, shoulder, knee and multi-site pain) in primary care.MethodsA systematic search… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
256
1
12

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 299 publications
(275 citation statements)
references
References 186 publications
6
256
1
12
Order By: Relevance
“…The Keele STarT MSK Tool has shown good predictive and discriminative ability in development and validation samples [38], identifying patients at low, medium or high risk of persistent MSK pain over 6months. Using systematic review and consensus methods, we also agreed evidence-based recommended matched treatment options for each of the risk subgroups [39,40].…”
Section: Introductionmentioning
confidence: 99%
“…The Keele STarT MSK Tool has shown good predictive and discriminative ability in development and validation samples [38], identifying patients at low, medium or high risk of persistent MSK pain over 6months. Using systematic review and consensus methods, we also agreed evidence-based recommended matched treatment options for each of the risk subgroups [39,40].…”
Section: Introductionmentioning
confidence: 99%
“…Non-specific low back pain is one of the most common chronic pain conditions (Balagu e et al, 2012), and exercise of the low back has been shown to be an effective physical therapy (Shi et al, 2018). Exercise and other forms of physical therapy are approved therapeutic treatment strategies in the rehabilitation of patients suffering from chronic pain including low back pain (Heneweer et al, 2009;Hooten et al, 2012;Babatunde et al, 2017;Geneen et al, 2017). Physical therapy reduces pain reactions in animals (Cobianchi et al, 2010;Shen et al, 2013;Sluka et al, 2013;Santos et al, 2014;Lima et al, 2017) and pain in humans (Naugle et al, 2012;Babatunde et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The large, independent evidence syntheses conducted for STarTMSK and ENHANCE research programmes, composed of systematic searches of bibliographic databases (including Cochrane database of systematic reviews, Database of abstracts of reviews of effects, Health Technology Assessment database, MEDLINE and EMBASE [using specific search filters to retrieve systematic reviews and clinical guidelines]), and evidence sources (Clinical Knowledge Summaries, Map of Medicine, TRIP Database, reference lists of included systematic reviews and guidelines, research stakeholders, and experts in the field) for the most recent, high quality reviews, clinical guidelines, and policy documents. The evidence syntheses used pre‐appraised evidence, such as clinical guidelines, policy documents, clinical evidence pathways, and evidence summaries, wherever possible as the starting point due to the broad topic areas being addressed, similar to the 6s pyramid model described by Dicenso et al The methods and results of these syntheses has been published elsewhere …”
Section: Methodsmentioning
confidence: 99%
“…The evidence syntheses used preappraised evidence, such as clinical guidelines, policy documents, clinical evidence pathways, and evidence summaries, wherever possible as the starting point due to the broad topic areas being addressed, similar to the 6s pyramid model described by Dicenso et al 26 The methods and results of these syntheses has been published elsewhere. 23,27 Information from evidence syntheses can be complex with multiple aspects to consider. Risk of bias and confounding, strength of recommendations, design of primary sources of data, magnitude of effect, level of precision, directedness, the dose response gradient of evidence, and consistency of results across sources of evidence may all affect interpretation of the evidence.…”
Section: Methodsmentioning
confidence: 99%